Mediatisation of politics - Marcinkowski, Frank (Javnost (Ljubljana), 2014)
This paper reviews the current state of the literature on the mediatisation of politics. Five common assumptions are being identified, which in my view form the core of a basic understanding of the concept. I discuss for each of these assumptions a number of further deliberations. My analysis is based on a theory of functionally differentiated societies. More precisely, I draw on the vision of modern societies that German sociologist Niklas Luhmann has introduced. According to his view the functional specialisation of social sub-systems is accompanied by an increased consolidation of performance relations between them, because self-referential fixation on the own function inevitably causes deficits in most other capacities. Against this background mediatisation is reconstructed as a response to a serious deficit of political systems: the notorious lack of public attention given to democratic politics within modern societies. This framework has several implications for the reasoning on mediatisation, which are outlined in the article.
Keywords: Družbeno komuniciranje; Politics; Social communication; Politika; communication; komuniciranje; politične komunikacije; mass media; množični mediji